Winds of change and paradigm shifts: Correspondence, distance and open learning - Andrew Higgins (Flexible Learning Association of New Zealand, 2012)
This paper uses the origins of and subsequent changes to correspondence education in Queensland and New Zealand to highlight how open and flexible learning practices are influencing the normal paradigm of educational teaching, learning and service delivery.